Determinants of financial reporting integrity in indonesian rural banks (bpr) - Dwi Prastowo Darminto; Muhammad Nurrasyidin; Eindye Taufiq; Winda Wulandari (Universitas Hayam Wuruk Perbanas, 2026)
This study examines the influence of corporate governance and internal control on financial reporting integrity in Indonesian Rural Banks (Bank Perekonomian Rakyat, BPR). Using a quantitative approach, data were collected through a survey of 85 respondents from BPRs and Sharia BPRs. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Descriptive statistics indicate that financial reporting integrity is at a very high level, reflecting transparency, accountability, reliability, and compliance in financial reporting. The hypothesis testing results demonstrate a positive and significant influence of corporate governance on financial reporting integrity (β = 0.538; p < 0.001), with corporate governance exerting a greater influence than internal control. Internal control also exhibits a positive and significant influence on financial reporting integrity (β = 0.307; p = 0.024). These findings confirm that financial reporting integrity is influenced by the quality of corporate governance and the effectiveness of internal control. They further suggest that strengthening corporate governance, optimizing internal control, and utilizing integrated information technology are key strategies for sustainably enhancing the quality and credibility of financial reporting in BPRs.